Electrochromic Material Based Poly-3,4 ethylene dioxythiophene: Polystyrene Sulfonate (PEDOT:PSS) Utilization as Smart Military Textiles: A Review - Sovian Aritonang (International Journal of Artificial Intelligence Research, 2022)
In this increasingly modern era, innovation in the main tool of the defense system (defense equipment) is the main support in the process of maintaining the sovereignty of the Unitary State of the Republic of Indonesia (NKRI). One of them is the innovation applied to TNI uniforms using electrochromic-based materials, namely PEDOT: PSS. PEDOT:PSS is known to be included in the classification of conductive polymers which have relatively good compatibility in terms of physical and chemical. The application of PEDOT:PSS as smart military textiles is carried out through a three-dimensional (3D) fabrication method, namely die-coating and ink-jet printing with a fabrication process speed of 20 meters per minute. Both of these methods are capable of producing high quality products, easy to design, and able to control the thickness of the substrate in the range of 80 to 750 nm